Premature Senescence and Telomere Shortening Induced by Oxidative Stress From Oxalate, Calcium Oxalate Monohydrate, and Urine From Patients With Calcium Oxalate Nephrolithiasis - Chuenwisad, Kamonchanok; More-krong, Pimkanya; Tubsaeng, Praween; Chotechuang, Nattida; Srisa-Art, Monpichar; Storer, Robin James; Boonla, Chanchai (Frontiers in Immunology, 2021)
Oxidative stress, a well-known cause of stress-induced premature senescence (SIPS), is increased in patients with calcium oxalate (CaOx) kidney stones (KS). Oxalate and calcium oxalate monohydrate (COM) induce oxidative stress in renal tubular cells, but to our knowledge, their effect on SIPS has not yet been examined. Here, we tested whether oxalate, COM, or urine from patients with CaOx KS could induce SIPS and telomere shortening in human kidney (HK)-2 cells, a proximal tubular renal cell line. Urine from age- and sex-matched individuals without stones was used as a control. In sublethal amounts, H2O2, oxalate, COM, and urine from those with KS evoked oxidative stress in HK-2 cells, indicated by increased protein carbonyl content and decreased total antioxidant capacity, but urine from those without stones did not. The proportion of senescent HK-2 cells, as indicated by SA-gal staining, increased after treatment with H2O2, oxalate, COM, and urine from those with KS. Expression of p16 was higher in HK-2 cells treated with H2O2, oxalate, COM, and urine from those with KS than it was in cells treated with urine from those without stones and untreated controls. p16 was upregulated in the SA-gal positive cells. Relative telomere length was shorter in HK-2 cells treated with H2O2, oxalate, COM, and urine from those with KS than that in cells treated with urine from those without stones and untreated controls. Transcript expression of shelterin components (TRF1, TRF2 and POT1) was decreased in HK-2 cells treated with H2O2, oxalate, COM, and urine from those with KS, in which case the expression was highest. Urine from those without KS did not significantly alter TRF1, TRF2, and POT1 mRNA expression in HK-2 cells relative to untreated controls. In conclusion, oxalate, COM, and urine from patients with CaOx KS induced SIPS and telomere shortening in renal tubular cells. SIPS induced by a lithogenic milieu may result from upregulation of p16 and downregulation of shelterin components, specifically POT1, and might contribute, at least in part, to the development of CaOx KS.